2006
DOI: 10.1111/j.1365-2613.2006.00486.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced prolidase activity and decreased collagen content in breast cancer tissue

Abstract: Adherent interactions between integrins and extracellular matrix (ECM) proteins play an important role in tumorigenicity and invasiveness. The major component of ECM is collagen that plays a central role in the interaction with integrins. The expression of certain collagenases (gelatinases) by tumour cells is one of the characteristic features of the so-called metastatic phenotype, presumably by breaking down ECM barriers as well by altering the ECM-cell interaction. Although extracellular collagenases initiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
45
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 40 publications
7
45
0
1
Order By: Relevance
“…3133 as well as a decrease in collagen content and deposition within other tumor tissues based on tissue type as well as age. 30,34,35 These results confirm that collagen content varies significantly between tumor tissue types, as well as within the stage of tumor development within a singular tissue type.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…3133 as well as a decrease in collagen content and deposition within other tumor tissues based on tissue type as well as age. 30,34,35 These results confirm that collagen content varies significantly between tumor tissue types, as well as within the stage of tumor development within a singular tissue type.…”
Section: Resultssupporting
confidence: 68%
“…Brain and prostate tissues were chosen to emphasize the significant collagen content variations between tissue types, as tissue such as breast tumors have been associated with decreased collagen content through tumor progression. 30 Analysis showed that collagen content changes with tumor progression dependent on tissue type. Brain tissue demonstrated an increase in collagen content as the tumor developed from Grade 1 to Grade 3, showing little collagen content at Grade 1.…”
Section: Resultsmentioning
confidence: 99%
“…Collagen is a major component of the extracellular matrix that serves as connective tissue that fills the interstitial space between cells [43]. Breast cancer tissues have been reported to have a significant decrease in collagen and an accompanying increase in collagen degradative enzyme activity [44]. Conversely, percent breast density is the strongest known, non-familial breast cancer risk factor, with the dense portion being primarily composed of collagen [45].…”
Section: Discussionmentioning
confidence: 99%
“…6 The central event in the progression of cancer is the secretion of MMPs, which are involved in matrix remodeling and cell growth. 7 Among the MMPs, prolidase is a manganese-dependent cytosolic exopeptidase, and it cleaves imidodipeptides and imidotripeptides with C-terminal proline or hydroxyproline. 8 It is the obligate enzyme, and its activity has been established in plasma, erythrocytes, leukocytes, and dermal fibroblasts, as well as in various organs including the kidney, brain, heart, thymus, liver, and uterus.…”
mentioning
confidence: 99%